Motivations to conduct research and burnout in medical education: a mixed methods study of students and residents - Devin Box; Skylar Healey; Stefani Mihilli; Kristen Barton; Ryan Degen; Mary Ott (Canadian Medical Education Journal)
Background: Burnout is on the rise in medical training as workload increases. One such demand is the pressure for research productivity earlier in training. However, little is known about the impacts of this trend and its mediating factors as trainees progress. Important influences may be motivation sources and supports, since intrinsic motivation is linked to well-being. This mixed methods study investigated associations between burnout and motivations for conducting research in a sample of medical students and residents in one academic centre.